An update on management of Acute Upper GI bleeding - Rowshon, AHM (Bangladesh Journal of Medicine, 2024)
Abnormal Bleeding from any site of the body is always an alarming condition. The Upper Gastrointestinal (GI) tract is one of the commonest sites and bleeding from these areas are potentially life threatening which may endanger life when occurs acutely with profuse in amount. Apart from many, Peptic Ulcer and Variceal bleeding from portal hypertension are commonly encountered as to the causes of acute upper GI bleeding. As part of ABC for an emergency patient, Intravenous access, infusion of fluid and transfusion of blood along with pharmacotherapies are commonly practiced strategies for the management of these type of patients and fortunately more than eighty percent patients are relieved from this acute situation with these treatments. Endoscopy and endoscopic therapy for varices and ulcer enhances the outcome of these patients. The timing and their appropriate use is also an utmost importance. In addition to poor visibility due to bloodshed and others, blood counts especially of haemoglobin level and platelet counts are of paramount importance to ensure safe and effective performance of these procedures. Coagulopathies genetically acquired , secondary to diseases or medications used by the patients are also important parameters to be considered before Endoscopic procedures. These procedures not only can appropriately diagnose the sites and nature of bleeding but also can assess the indications and type of required endoscopic interventions. The potential chances of re-bleeding and timing of follow up can also be assessed by endoscopy. In addition to Esophageal Band Ligation, Sclerotherapies, Glue injection and Clipping of bleeding vessels, modern modalities of Endo sonic procedures through vascular access are in practice for refractory bleeding. Use of broad-spectrum prophylactic antibiotics has been found to yield better prognosis in terms of morbidity and mortality than it has been thought of for long time. Encrporating these relatively new updated protocols and procedures, the outcome of Acute Upper Gastrointestinal bleeding can be improved. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 141